2021
DOI: 10.15587/1729-4061.2021.225007
|View full text |Cite
|
Sign up to set email alerts
|

Devising an express method for estimating the quality of colostrum and its components based on electrical conductivity

Abstract: This paper reports the development of an express method for assessing the quality of biologically active substances derived from colostrum. We tested the hypothesis that there may be a dependence between the amount of protein that is part of the colostrum and its characteristic (a difference in molecular masses) and electrical conductivity. It has been shown that the colostrum contains several hundred proteins: it depends on the individual characteristics of cattle. The removal of lipids was accompanied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The electric conductivity of components of colostrum, taken from different producers. It is known, that lipids manifest dielectric properties [18], and their elimination is accompanied by an electric conductivity increase as it was demonstrated above [15]. Lipids elimination from colostrum demonstrated that 92 % of proteins, 7.69 % of carbohydrates and 0.31 % of vitamins and other substances, including ions, took place in skim milk counting for solid residue (Fig.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The electric conductivity of components of colostrum, taken from different producers. It is known, that lipids manifest dielectric properties [18], and their elimination is accompanied by an electric conductivity increase as it was demonstrated above [15]. Lipids elimination from colostrum demonstrated that 92 % of proteins, 7.69 % of carbohydrates and 0.31 % of vitamins and other substances, including ions, took place in skim milk counting for solid residue (Fig.…”
Section: Resultsmentioning
confidence: 78%
“…Such biophysical method as electric conductivity measuring may be used as integral parameters of multicomponent dynamic biological mixtures. This approach allows to evaluate the total number of charged ions and other molecules in colostrum [15]. The most biological activity in metabolism regulation mechanisms is inherent to peptides and low-molecular proteins.…”
Section: Introductionmentioning
confidence: 99%
“…However, interest in this promising method was somewhat lost due to the difficulty of interpreting the obtained results. Our investigations have shown that the electrical conductivity of biological systems is affected not only by the ionic composition, but also by the presence of lipids and membrane structures, and the ratio between high and low molecular weight proteins in biological systems [12]. The conductivity index can reflect the peculiarities of the organization of biological systems [13].…”
Section: Introductionmentioning
confidence: 86%
“…It was previously shown that, along with the ionic composition, the parameters of electrical conductivity are significantly influenced by lipid components and the proteins composition [12]. Thus, the removal of lipid components from the medium was accompanied by an increase in electrical conductivity.…”
Section: The Electric Conductivity Of the Bmcs In Young And Old Intact Animalsmentioning
confidence: 99%
See 1 more Smart Citation